Local Instability Analysis for Axial Compressive Steel Columns - Nguyen, P. C. (Engineering, Technology & Applied Science Research, 2022)
This study presents a nonlinear analysis method for steel columns considering local instability under axial compression. The stress-strain relationship of steel is developed while considering the effects of local instability utilizing the energy principles. The second-order effects are considered by stability functions, while the plasticity of steel is captured by a fiber finite element method. Nonlinear equilibrium equations are solved by the generalized displacement control method. As a result, the proposed formulations are effective, accurate, and reliable in predicting the load-carrying capacity and local instability of steel columns.